Reversão de recursos obtidos de irregularidades trabalhistas : um olhar sobre as externalidades positivas - Pinheiro, Silvio Simplicio (2024)
In addition to its role of preventing and correcting labor irregularities committed by employers, the Labor Prosecutor's Office (MPT) can also play an important social role in society. This is due to the possibility of reversing resources resulting from public civil actions or conduct adjustment terms, which allows the direct allocation of resources to local entities and projects, benefiting the community where the labor damages occurred, instead of being directed to the federal government. The reversal of resources by the MPT is a practice that can, as a means of investment, generate positive impacts in communities affected by labor irregularities. This research examines how the Labor Prosecutor's Office can enhance the positive externalities generated by reversing resources obtained from labor irregularities. Conceptually, concepts related to economic and social development, law and externalities were used, focusing on a public service. Regarding the methods, this is qualitative research, of a descriptive and exploratory nature through a case study. Data were collected through interviews, non-participant observation and documents and analyzed using narrative analysis and document analysis techniques. Results indicated that the local resource reversion has been consolidated as a relevant practice in the MPT/ES, by directing resources to projects in the areas of health, education, social inclusion, among others. In addition to identifying the common challenges in the resource reversion process, the main criteria adopted in the allocation of resources were also identified. Based on the characteristics identified, a set of proposals are presented aiming at improving the process and overcoming the identified challenges, aiming at enhancing this practice in order to maximize positive externalities. The main technical product generated from this research was a didactic and instructional material (Training Course) aimed at optimizing the direction of resource reversion to locations affected by labor damages, through awareness and process improvement. The proposed Course can be applied to the MPT throughout the national territory, strengthening and enhancing the relevant role of this public agency in generating positive externalities through resource reversion